Big book of emergency department psychiatry - Balan, Yener Aysun; Lentz, Christopher Bryant; Murrell, Karen (Psychiatrist) (Boca Raton : Taylor & Francis, 2018)
"This book focuses on the operational and clinical strategies needed to improve care of Emergency Psychiatric patients. Boarding of psychiatric patients in ED's is recognized as a national crisis. The American College of Emergency Physicians identified strategies to decrease boarding of psychiatric patients as one of their top strategic goals. Currently, there are books on clinical care of psychiatric patients, but this is the first book that looks at both the clinical and operational aspects of caring for these patients in ED setting. This book discusses Lean methodology, the impact of long stay patients using queuing methodology, clinical guidelines and active treatment of psychiatric patients in the ED."--Provided by publisher.
chapter 1 Front Line Perspectives -- chapter 2 Structural Approaches to Patient Centered Care -- chapter 3 Clinical Care -- chapter 4 Specialized Population Care -- chapter 5 Methods for Operational Improvement.
"A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc."
Keywords: Psychiatric emergencies